Oxidative stress‐induced lncRNA CYLD‐AS1 promotes RPE inflammation via Nrf2/miR‐134‐5p/NF‐κB signaling pathway. Issue 10 (27th September 2022) - Du, Han; Huang, Zixin; Zhou, Xin; Kuang, Xielan; Long, Chongde; Tang, Han; Zeng, Jingshu; Huang, Hao; Liu, Huijun; Zhu, Binbin; Fu, Licheng; Hu, Ke; et al.
Abstract: Oxidative stress‐induced damage to and dysfunction of retinal pigment epithelium (RPE) cells are important pathogenetic factors of age‐related macular degeneration (AMD); however, the underlying molecular mechanism is not fully understood. Long noncoding RNAs (lncRNAs) have important roles in various biological processes. In this study, using an oxidative damage model in RPE cells, we identified a novel oxidation‐related lncRNA named CYLD‐AS1. We further revealed that the expression of CYLD‐AS1 was increased in RPEs during oxidative stress. Depletion of CYLD‐AS1 promoted cell proliferation and mitochondrial function and protected RPE cells against hydrogen peroxide (H2 O2 )‐induced damage. Mechanistically, CYLD‐AS1 also regulated the expression of NRF2, which is related to oxidative stress, and NF‐κB signaling pathway members, which are related to inflammation. Remarkably, these two signaling pathways were mediated by the CYLD‐AS1 interactor miR‐134‐5p. Moreover, exosomes secreted by CYLD‐AS1 knockdown RPE cells had a lower proinflammatory effect than those secreted by control cells. In summary, our study revealed that CYLD‐AS1 affects the oxidative stress‐related and inflammatory functions of RPE cells by sponging miR‐134‐5p to mediate NRF2/NF‐κB signaling pathway activity, suggesting that targeting CYLD‐AS1 could be a promising strategy for the treatment of AMD and related diseases.